2020
DOI: 10.1152/physrev.00013.2020
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasmin(ogen) as a Common Risk Factor for COVID-19 Susceptibility

Abstract: Patients with hypertension, diabetes, coronary heart disease, cerebrovascular illness, chronic obstructive pulmonary disease, and kidney dysfunction have worse clinical outcomes when infected with SARS-CoV-2, for unknown reasons. The purpose of this review is to summarize the evidence for the existence of elevated plasmin(ogen) in COVID-19 patients with these comorbid conditions. Plasmin, and other proteases, may cleave a newly inserted furin site in the S protein of SARS-CoV-2, extracellularly, which increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
391
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(410 citation statements)
references
References 102 publications
(136 reference statements)
6
391
0
13
Order By: Relevance
“…9 Early data from the United States have suggested that endogenous protease plasmin acts on COVID-19 virus by cleaving a newly inserted furin site in the S protein portion of the virus, resulting in increased infectivity and virulence. 10 Intravenous tranexamic acid, commonly used as a hemostatic agent in rhinoplasty surgery, may suppress this conversion and could be repurposed for the treatment of COVID-19. 9 Postoperative care Limiting face-to-face interaction with patients will remain a challenge in the immediate postoperative period.…”
Section: Intraoperative Carementioning
confidence: 99%
“…9 Early data from the United States have suggested that endogenous protease plasmin acts on COVID-19 virus by cleaving a newly inserted furin site in the S protein portion of the virus, resulting in increased infectivity and virulence. 10 Intravenous tranexamic acid, commonly used as a hemostatic agent in rhinoplasty surgery, may suppress this conversion and could be repurposed for the treatment of COVID-19. 9 Postoperative care Limiting face-to-face interaction with patients will remain a challenge in the immediate postoperative period.…”
Section: Intraoperative Carementioning
confidence: 99%
“…25 It is postulated that plasminogen may increase the pathogenicity of SARS--CoV-2 by increasing its ability to bind to ACE2 and thereby facilitate its penetration into host cells. 26 However, according to the theory of Fang et al, 27 in diabetic or hypertensive patients who result in alteration in ACE2-related signaling pathways and subsequently cause local inflammation. 24,51 The second possible mechanism is acute cardiac injury due to the cytokine storm, which is triggered by an imbalance between type 1 and type 2 helper T cells.…”
mentioning
confidence: 99%
“…44 In addition, increased levels of plasminogen are found in bronchoalveolar lavage in patients with acute respiratory distress syndrome. 26,45 Thus, elevated levels of D -dimers appear to be the result of both excessive systemic inflammatory response and increased fibrinolysis due to increased plasmin concentration. Patients with COVID-19 also present other coagulation abnormalities such as increased levels of fibrinogen and fibrin and fibrinogen degradation products, and reduced levels of antithrombin, when compared to the healthy control population.…”
mentioning
confidence: 99%
“…The SARS-CoV-2 relies on the host cell proteases to cut its S protein in two parts thus forming Nterminal part which recognizes ACE2 receptor and C-terminal part involved in the viral entry which must be further cleaved by furin and/or other furin-like enzymes [17]. It has been shown that plasmin is also capable to cleave furin sites [19] and that individuals with elevated plasmin demonstrated higher susceptibility to COVID-19 [20]. In addition to plasmin, S protein of coronaviruses may be cleaved by other airway proteases such as trypsin-1 and TMPRSS11a [20].…”
mentioning
confidence: 99%
“…It has been shown that plasmin is also capable to cleave furin sites [19] and that individuals with elevated plasmin demonstrated higher susceptibility to COVID-19 [20]. In addition to plasmin, S protein of coronaviruses may be cleaved by other airway proteases such as trypsin-1 and TMPRSS11a [20].…”
mentioning
confidence: 99%